Tetraazacoronenes and their dimers, trimers and tetramers [data] - Eichelmann, Robert; Ballmann, Joachim; Gade, Lutz H. (Universität, 2024)
Tetraazacoronenes were synthesized from bay-functionalized tetraazaperylenes by Zr-mediated cyclization and four-fold Suzuki-Miyaura cross coupling. In the Zr-mediated approach, an η4-cyclobutadiene-zirconium(IV) complex was isolated as an intermediate to cyclobutene-annulated derivatives. Using bis(pinacolatoboryl)vinyltrimethylsilane as a C2 building block gave the tetraazacoronene target compound along with the condensed azacoronene dimer as well as higher oligomers. The series of extended azacoronenes show highly resolved UV/Vis absorption bands with increased extinction coefficients for the extended aromatic cores and fluorescence quantum yields of up to 80 % at 659 nm.